INDONESIAN YOUTH’S PERSPECTIVE TOWARDS LGBT - Yam - Saroh; Mei Relawati (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2017)
PERSPEKTIF ANAK MUDA TERHADAP LGBTAbstractThe LGBT community is a group of people who are engaged in same-sex sexual activity. Concerning about religion, Indonesian still consider LGBT as a sin, therefore, they do not approve same-sex marriage. However, this perspective has questioned now since in fact, some start to be open minded and accept LGBT’s existence, even few are involved in the LGBT communities. One of them is Gaya Nusantara, which is initiated by Indonesian gay lived in Surabaya. This community functions as a forum for Indonesian gay to share ideas and experience aims to actualize themselves. Regarding to this phenomenon, this study was arranged using a case study research which aimed to figure out the Indonesian youth’s perspective towards LGBT. The researchers used questionnaire as the instrument to get the data with 4 questions covered the perspective of the youth. The subject of the research was 100 hundred youth from 14 cities and towns in Indonesia. The significance of the study informed the LGBT phenomenon among the youth to Indonesian parents and teachers as someone who take responsibility in educating the children so that they are not influenced by this social phenomenon.Key word:LGBT, LGBT perspective, Indonesian youth’sperspective AbstrakKomunitas LGBT (lesbian, gay, biseksual, transgender) adalah sekelompok orang yang terlibat dalam aktivitas seksual sesama jenis. Menyangkut soal agama, Indonesia masih menganggap LGBT sebagai sebuah dosa.Oleh karena itu, mereka tidak menyetujui pernikahan sesama jenis. Namun, perspektif ini saat ini masih dipertanyakan karena pada kenyataannya beberapa mulai berpikiran terbuka dan menerima keberadaan LGBT, bahkan ada beberapa yang terlibat dalam komunitas LGBT. Salah satunya adalah Gaya Nusantara yang digagas oleh gay Indonesia yang tinggal di Surabaya. Komunitas tersebut berfungsi sebagai forum bagi gay Indonesia untuk berbagi ide dan pengalaman yang bertujuan untuk mengaktualisasikan diri. Sehubungan dengan fenomena tersebut, studi ini diatur menggunakan penelitian studi kasus yang bertujuan untuk mengetahui perspektif pemuda Indonesia terhadap LGBT. Peneliti menggunakan kuesioner sebagai instrumen untuk mendapatkan data dengan 4 pertanyaan tertutup tentang perspektif pemuda. Subjek penelitian adalah 100 ratus pemuda dari 14 kota besar dan kota kecil di Indonesia. Signifikansi penelitian menginformasikan fenomena LGBT di kalangan pemuda untuk orang tua dan guru Indonesia sebagai seseorang yang bertanggung jawab dalam mendidik anak-anak agar mereka tidak dipengaruhi oleh fenomena sosial ini.Kata kunci:LGBT,perspektif LGBT, perspektif pemuda Indonesia